P.111 Large partially thrombosed posterior circulation aneurysms: A treacherous masquerader of benign brain tumors. (17th June 2016) - Alizadeh Vakili, N; Chiu, A; Drake, B; Montanera, W; Bharatha, A; Marotta, T; Sarma, D; Spears, J
Abstract : Background: On imaging, thrombosed aneurysms can be mistaken for tumor with potentially disastrous consequences.Methods: We present two cases of aneurysms mimicking tumor.Results: Patient 1 (6 months of left-sided facial weakness): MRI demonstrated a 3.3 cm, T1-isotense, T2-hypertense heterogeneous enhancing mass favored to represent a CPA schwannoma. Biopsy revealed a thrombosed aneurysm. DSA subsequently revealed an area of contrast penetration, treated by parent artery (AICA) obliteration. Two-year follow-up revealed stable occlusion with reduced mass effect. Patient 2 (1 year of headaches): Imaging demonstrated an extra-axial T1-mixed, T2-hyperintense heterogeneously enhancing mass in the left CPA adjacent to the vertebral artery, enlarging from 1.7 cm to 3.2 cm over 2 years. DSA revealed slow, crescentic filling with suggestion of arborisation distally. Patient deteriorated due to mass effect requiring a VP shunt and passed away from SAH 3 months later. Imaging review revealed crescentic filling of the remnant lumen on CE-MRA and signal voids on T2 in both cases, which may suggest the aneurysm diagnosis. However our cases did not have other features such as lamellated thrombus or pulsation artifact.Conclusions: Central contrast enhancement does not necessarily preclude the diagnosis of thrombosed aneurysm. The possibility of revascularization or penetration of contrast through the thrombus in giant aneurysms needs to be considered.